SUBCOLLOQUIAL MESURATIVE PHRASEOLOGICAL UNITS AS A SEMANTIC CENTER - Nodirjon Otakulov (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The article examines the most frequent lexical and phraseological units with the numerals "one" and "two" used in the subcolloquial mesurative phraseological units of the French, Uzbek and Russian languages as a semantic center. An analysis of the generality and specificity was carried out in the meanings of the subcolloquial mesurative phraseological units of the compared languages. This analysis involves the study of the semantics of subcolloquial mesurative phraseological units, the mechanisms of nomination and associative links existing in them, the consciousness and properties of the mentality of the three cultures.The considered subcolloquial mesurative phraseological units of the compared languages fully reflect the linguistic personality of the French, Uzbek and Russian cultures, reveal their value in the picture of the world and contribute to the definition of their commonality and specificity.